Local Government Efforts to Prevent Stunting at the Village Level - Syahrul Syahrul; Ikhsan Ikhsan (Ilomata International Journal of Social Science, 2022)
Stunting is a chronic disease that occurs in toddlers due to long-term malnutrition. The condition of stunting in toddlers is caused by various things, including problems in nutrition, hygiene, health and social understanding for children. This study aims to determine the local government's stunting prevention efforts in children at the village level, Sungai Mas District, West Aceh Regency. The research method used is a descriptive survey using a qualitative approach that focuses on the phenomena and problems during the survey. The research results show that the government's efforts to prevent child stunting at the village level, Sungai Mas District, and West Aceh Regency are carried out through several stages: the prevention planning stage, program implementation, and HR competency improvement and stunting data reporting. Based on stunting prevention efforts, it was found that the implementation of stunting prevention efforts had been carried out but had not been carried out optimally according to the previously designed plan. However, there has been a decrease in data on the number of confirmed stunting children in the last three months.